2018
DOI: 10.1037/cou0000273
|View full text |Cite
|
Sign up to set email alerts
|

Attachment-security prime effect on skin-conductance synchronization in psychotherapists: An empirical study.

Abstract: Physiological synchronization (PS) is a phenomenon of simultaneous activity between two persons' physiological signals. It has been associated with empathy, shared affectivity, and efficacious therapeutic relationships. The aim of the present study was to explore the possible connections between PS and the attachment system, seeking preliminary evidence of this link by means of an experimental manipulation of the sense of attachment security in psychotherapists according to a protocol by Mikulincer and Shaver … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 56 publications
0
20
0
Order By: Relevance
“…Karvonen, Kykyri, Kaartinen, Penttonen & Seikkula (2016) also reported evidence of EDA concordance in a setting of systemic couple therapies with two therapists. Palmieri et al (2018) found higher EDA synchrony in clinical interviews when the interviewer had received a secure-attachment prime. Coutinho et al (2018) supported the significant synchrony findings in a sample of romantic couples, yet not with the concordance index but with the cross-correlational method of surrogate synchrony (concordance and surrogate synchrony are introduced in the methods section below).…”
Section: Research On Physiological Synchrony In Psychotherapy and Psymentioning
confidence: 80%
“…Karvonen, Kykyri, Kaartinen, Penttonen & Seikkula (2016) also reported evidence of EDA concordance in a setting of systemic couple therapies with two therapists. Palmieri et al (2018) found higher EDA synchrony in clinical interviews when the interviewer had received a secure-attachment prime. Coutinho et al (2018) supported the significant synchrony findings in a sample of romantic couples, yet not with the concordance index but with the cross-correlational method of surrogate synchrony (concordance and surrogate synchrony are introduced in the methods section below).…”
Section: Research On Physiological Synchrony In Psychotherapy and Psymentioning
confidence: 80%
“…Even more serious is the fact that the terminological ambiguity extends to the methodologies. While the term concordance is mainly associated to the procedure described in Marci and Orr ( 2006 ), Marci et al ( 2007 ), the same term has been previously employed to describe simple correlation (Di Mascio et al, 1955 ), and the same procedure has been also called physiological synchronizatio n (Palmieri et al, in press ), skin conductance resonance (Stratford et al, 2009 ), embodied synchrony (Karvonen et al, 2016 ), and therapeutic index (Stratford et al, 2012 ). It is imperative that new contributions propose and rely on operationally defined procedures, that explicitly point to the type of IP assessed.…”
Section: Resultsmentioning
confidence: 99%
“…Some early studies showed evidence for autonomic concordance between clients and therapists (e.g., DiMascio et al, 1957), a finding that has been explored further more recently (e.g., Marci et al, 2007;Villmann et al, 2008;Karvonen et al, 2015;Seikkula et al, 2015Seikkula et al, , 2018Kodama et al, 2018;Tschacher and Meier, 2020). Findings from these studies are mixed; however, one finding that has been shown across several studies on psychotherapy sessions (as well as in studies of simulated sessions, e.g., Marci and Orr, 2006;Messina et al, 2013;Palmieri et al, 2018) is a correlation between ratings of empathy and the degree of physiological linkage between therapist and client. Despite some such relatively consistent findings, research on interpersonal physiology in psychotherapy is still in its infancy and is characterized by methodological and conceptual diversity which makes it difficult draw any definite overarching conclusions, other than that there is evidence of autonomic linkage between therapist and client during sessions (Kleinbub, 2017).…”
Section: Interpersonal Physiology and Psychotherapy Processmentioning
confidence: 99%